Danzando en pandemia: análisis metodológico de los procesos implementados en el colegio George Washington School en estudiantes del ciclo dos en el año 2021 (2022)
Dancing in a pandemic: methodological analysis of the processes taught to students of the George Washington school, cycle 2, this is a degree work based on a pedagogical artistic experience obtained in the institution, where the needed to implement the virtual didactic teaching in the performing arts, specially dance was seen. Carrying out new methodologies in virtual classes implementing innovative technological tools of interest for students. As a results, the successful process of the students of the cycle 2 (Third, fourth and fifth grade), where the interest and the methodology handled during the virtual work are seen. The methodologies used on this work are developed from the didactic of the performing arts specially dance and the choreography games within virtuality and the technologies used within ICT in education.